Perbedaan Pengaruh Antara Penggunaan Abm Kruk Dengan Prostesis Terhadap Mobilitas Pasien Pasca Amputasi Transtibial - Yopi Harwinanda Ardesa; Cica Tri Mandasari Ningsih (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: To know the difference between using crutches utch and prosthesis on patient mobility after transtibial amputation, Research Design is a type of pre-experimental study with static comparison group research design. The subjects of this study were transtibial amputation patients divided into two groups. Each group consists of 15 people. Methods: The type of group in this study is a paired group in which one person gets two treatments. PT Kuspito Ortotik Prostetik Karanganyar, Time: June to October 2017. One person gets two treatments in the form of Kruk and prosthesis, prosthesis user will be tested with AMPpro test and Kruk user usage will be tested using AMPnopro, Measurements: AMPpro 20 test and AMPnopro 21 test, different test with Wilcoxon Signed Ranks Test. Results: Showed an average balance in the crutches group (15,32) while the mean balance was in the prosthesis group (45,38). The result of the statistical test with man Whitney shows p-value 0,000 <0,05 so there is a difference in the effect of crutch and prosthesis on patient mobility after transtibial amputation. Conclusion: The results of this study indicate that there is a difference between the use of Kruk and the prosthesis of mobility, the mobility of the prosthesis user has a higher level at the level of k-4, while the Kruk level is the k-3 level.